Factors influencing hand hygiene compliance of healthcare students - Elsafi, Salah H; Al-Howti, Shahad Y (International Journal of Infection Control, 2019)
Hand hygiene is the most effective way to control healthcare-associated infections. The aim of this study is to measure the hand hygiene awareness and practices in relation to various variables among the healthcare students. A structured validated questionnaire was completed by the participants to assess their awareness and compliance with hand hygiene. The average knowledge score of 500 students was 6.24/10 with a significant difference between various departments (p = 0.001). Knowledge significantly increased by advanced years of study. The average attitude and practice scores were 6.96 and 5.13, respectively with significant differences only in practice between various departments but not within other variables. Despite an overall good knowledge and attitude, the compliance of hand hygiene was generally poor. These findings suggested that other factors than knowledge and attitude might play a role in compliance. Although there appears to be a direct correlation with knowledge and year of study (Correlation coefficient r = 0.96) a weaker correlation value was detected with attitude (r = 0.02). Conversely, we detected a negative correlation between compliance with hand hygiene and the year of study (r = -0.55). In contrast to many other studies, no gender difference in attitude and practice in this study.